ASSOCIATION OF MICROALBUMINURIA AND DIABETIC RETINOPATHY IN PATIENTS WITH TYPE II DIABETES MELLITUS - SARAVANAN AKSHARA; NITHYAPRIYA CHINNARAJU; ADARSH S NAIK; JEEVITHAN SHANMUGAM (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Diabetes mellitus (DM) is a long-term metabolic condition marked by decreased synthesis and thereby function of insulin, which can result in serious side effects such as nephropathy and diabetic retinopathy. Diabetic nephropathy plays a significant role in end-stage renal disease, and diabetic retinopathy is one of the main preventable causes of blindness. In patients with type 2 DM, this study intends to investigate the relationship between diabetic retinopathy and microalbuminuria while considering other risk factors such as age, duration of diabetes, and glycemic management. Methods: Ninety-seven patients with type 2 DM and diabetic retinopathy participated in this hospital-based cross-sectional study. Based on the American Academy of Ophthalmology diabetic retinopathy disease severity scale, participants were categorized. Spot urine samples were used to find out microalbuminuria, and Chi-square and t-tests were used to examine correlations between microalbuminuria, diabetic retinopathy, and other clinical and demographic variables. Results: Microalbuminuria was shown to be significantly correlated (p<0.001) with the severity of diabetic retinopathy. In addition, microalbuminuria was significantly associated with older age (p=0.002) and longer diabetes duration (p<0.001). Nevertheless, no meaningful correlations were discovered between sex, treatment history, or diabetes in the family history and microalbuminuria. Conclusion: The findings highlight the importance of strict monitoring of microalbuminuria in patients with diabetic retinopathy, especially in the elderly and with long-duration diabetes. Early detection and management of diabetes and strict control of glycemic levels will help to prevent further complications.